The effect of an Educational design based on deep learning strategies on academic achievement in biology and future thinking among first-year middle school female students - Jayed Al-Rikabi, Qusay Qasim (Journal of Tikrit University for Humanities, 2024)
The current research aims to identify the effect of an educational design based on deep learning strategies on academic achievement in biology and future thinking among first-year middle school female students. To verify the goal of the research and test its hypotheses, the researcher used an experimental design with partial control (an experimental group and a control group). The sample consisted of (40) female first-year intermediate students, with (20) female students in each group. The experimental group was studied according to the educational design of deep learning strategies, and the control group was studied according to the usual method. The researcher rewarded the two research groups in the variables of age and intelligence. Testing previous information and future thinking. Then he determined the scientific material for the study, formulated the behavioral objectives, and prepared teaching plans for the two research groups. He also prepared two tools, the first an achievement test consisting of (42) three-alternative multiple choice items, and the second a future thinking scale consisting of (38). ) paragraph, and after preparing the two tools, they were applied to the two groups, and after analyzing the data statistically, the researcher concluded that the experimental group that was taught according to deep learning strategies outperformed the control group that was taught in the usual way in the achievement test and the future thinking scale, and in light of these results, he The researcher developed a number of recommendations and proposals.